Kerala Land and Culture - (:unkn) unknown (My University, 2019)
Kerala is known as God’s own country because of its unique geographical position & natural features and cultural diversities. It has rich culture, creative art forms, bio-diversities and many similar other features. This has to be described systematically. In this book, there is an earnest and sincere attempt to describe the cultural identities and value systems historically. Several aspects of Kerala life including Geographical Features, Pre-historical Culture, Sangam Literature, Agriculture, Western Domination, Missionaries & Education, Kerala Renaissance, Women Empowerment, Tribes, Art Forms and Beliefs, Religions, Language & Literature as well as Media of Kerala have been narrated in the book.
Keywords: Malayalam